Moscow, Lithuania, the Horde and the last testaments of Vasily I - Polekhov S.V. (Золотоордынское обозрение)
Research objectives: To ascertain why Grand Prince Vasily I of Vladimir and Moscow had to make his will twice in the last years of his reign and ask his father-in-law, Grand Duke Vytautas of Lithuania, to confirm it, and what the role played by the Golden Horde in these events was. Research materials: Testaments of Vasily I and other Rurikids of Moscow, Russian chronicles, letters of Vytautas and dignitaries of the Teutonic Order. Results and novelty of the research: According to the research, the reason for Vasily I drawing up the third testament between 1423 and 1425, shortly after his second testament approved by the guarantor, Grand Duke Vytautas of Lithuania, was the granting of a yarliq by Khan Ulugh Muhammad to Prince Daniil Borisovich that meant the restoration of the Principality of Nizhny Novgorod independent of Moscow. The paper provides arguments that by doing so, Ulugh Muhammad was acting independently. Although he was Vytautas’ ally, his action was contrary to the intentions of the Grand Duke of Lithuania who was interested in seeing his underage grandson Vasily Vasil’evich’s succession to the throne because Vasily I’s brother Yury Dmitrievich, an ally of Vytautas’ rival Švitrigaila, could aspire to it. Despite the struggle for power in the Horde in the early 1420s, Ulugh Muhammad seems to have had enough power to help Daniil Borisovich realize his claim to Nizhny Novgorod. Since Vytautas was not able to provide Vasily Vasil’evich with Nizhny Novgorod as a part of Vasily I’s possessions, which showed the limits of his possibilities regarding the Horde, the third testament was made in a different way than the second one: at the beginning it was signed by Metropolitan Photios, then sealed by Vasily I and his three brothers, and at the very end by Vytautas.